EFL Students' Perspectives toward Project-Based Learning in Vocational High Schools - Amalia, Sonia Intan Yazid; Degeng, Putu Dian Danayanti; Razali, Khairil Azwar (Universitas Pendidikan Mandalika, 2024)
In the world of education, there are many methods that can be used in the learning process. In the 21st century, the project based learning method is often used because it is in accordance with the current curriculum. This research aims to describe EFL students' perspectives toward project-based learning in vocational high school. Researchers used a mixed method by collecting data using a questionnaire and semi-structured interviews. The subjects of this research were 59 students of SMK PGRI 3 Malang from the animation and design, communication and visual department. The research results revealed that more than 71% of students gave positive responses to this method which was considered effective for increasing understanding, activeness, motivation and speaking ability in vocational high school English classes. Students feel they can increase understanding by discussing with friends when working on projects. Apart from that, during discussions students feel more active in exchanging knowledge with each other in the group. Students also feel that project-based learning makes work easier and more fun because they are done together. In addition, students feel that their speaking skills have improved after making several presentations, and they are more confident in speaking in front of the class. Therefore, project-based learning is considered to be an appropriate method for learning English in vocational high schools. This research is expected to provide new knowledge for readers regarding EFL students' perspectives toward project-based learning in vocational high school. This is so that the implementation of project-based learning in the future can be more optimal than before.